Determinants of Compliance with Standard Practices of Pesticide Use Among Cocoa Farmers in Southwestern Nigeria - Anthony Eghe Agbongiarhuoy; Ogbaraeno Pippy Fawole (Indonesian Coffee and Cocoa Research Institute, 2020)
Cocoa production in Nigeria is limited due to pests and diseases. In an attempt to control these, farmers apply pesticides which leave chemical residue in cocoa beans. There are established standard practices to address the abuse in use of pesticides. However, there is dearth of information on factors that predispose cocoa farmers to comply with approved standard practices. Therefore, determinants of compliance with standard practices of pesticide use by cocoa farmers in Southwestern Nigeria were investigated. A three-stage sampling procedure was used to select respondents. Two cocoa producing States (Oyo and Ondo) were purposively selected. Two Local Government Areas (LGAs) known for cocoa production were selected from each state. Systematic random sampling was used to select 10% of registered farmers to give 354 respondents. Interview schedule was used to collect data on respondents’ variables. Data were analysed using descriptive statistics and multiple regression at  0.05. Most farmers were male (70.3%) and had secondary education (31.9%). Respondents’ age and farmingexperience were 58.0 and 27.0 years, respectively. Farmers’ yield and annual income were 0.449 tonnes obtained from an average of 6.25 ha cocoa farm size andN1,331,519.60 equivalent to 3,698.67, respectively. Determinants of compliance with standard practices of pesticides use for both dosage and procedure were determined by age ( = -0.20), income ( = 0.15), exposure to information (= 0.36), constraints ( = -0.27) and accessibility to approved pesticides ( = -0.11). Exposure of farmers to information and realising more money motivates them to purchase approved pesticides that will aid compliance with standard practices. As age of farmer increases, the ability to comply will be limited. A farmer who is constraint with poor access to recommended pesticides will go for unapproved types which are against compliance. Concerted efforts should be put in place by relevant bodies to ensure sustainable income, information access for respondents in order to adhere to recommended protocols and enhanced cocoa yield.